Zbirka vaj za predmet Metode raziskovanja - Tominc, Polona; Čančer, Vesna; Rožman, Maja (University of Maribor Press, 2018)
Collection of Exercises for the Research Methods Course. The collection of exercises is intended primarily to guide students how to use the SPSS statistical software package for selected statistical methodologies that fall within the quantitative part of the course Research methods, at the Master’s study program Economic and Business Science, at the University of Maribor, Faculty of Economics and Business. The material is a supplement to the basic study literature for the quantitative part of the course and to the methodological approaches discussed at lectures. The material is intended for students to study and understand the classification of statistical quantitative methods, depending on the characteristics of the collected data and research assumptions. The substantive analysis is presented in order to guide students how to correctly interpret the obtained results with the SPSS software. An integral part of the active participation of students at lectures is an interpretation of the results obtained to support business decision-making. We wish students a successful use of the methodologies discussed.